A privacy‐preserving biometrics based authenticated key agreement scheme using ECC. (30th March 2020) - Qi, Mingping; Chen, Jianhua
Summary: To ensure secure communication over the insecure public network, this work presents a privacy‐preserving biometrics‐based authenticated key agreement scheme using elliptic curve cryptography, making full use of the advantages that the biometrics can be used to uniquely identify a particular human, and the elliptic curve cryptography can provide the same level security with far less key size compared with other public key cryptography. The proposed scheme realizes the mutual authentication of participants, session key agreement, and various security properties and also can resist kinds of known attacks. Moreover, the proposed scheme has perfect user experience in the aspect of changing password by not interacting with the server. In addition, the security features of our new designed scheme are formally proved under the widely used BPR adversary model. Therefore, from the viewpoint of the authors, the proposed scheme can be considered as the authenticated key agreement scheme for mobile users. Abstract : This work presents a privacy‐preserving biometrics based authenticated key agreement scheme using ECC, which realizes the mutual authentication of participants, session key agreement, and various security properties, and also can resist kinds of known attacks. Moreover, the proposal scheme has perfect user experience in the aspect of changing password by not interacting with the server. In addition, the security features of our new designed scheme are formally proved under the widely used BPR adversary model.